Does environmental information disclosure drive corporate sustainable growth? A new insight into U-shaped relationship - Zhang, Jinsong; Wang, Mengmeng (Frontiers in Ecology and Evolution, 2023)
Due to the increasing rate of economic development and the increasingly serious problem of environmental degradation, environmental information disclosure has become an important basis for promoting carbon peaking and carbon neutrality, and an important way for enterprises to carry out green governance to achieve sustainable development. This study uses empirical research methods to analyze the relationship between environmental information disclosure and corporate sustainable growth in the context of green governance using panel data of Chinese A-share listed companies in Shanghai and Shenzhen from 2012 to 2021. The empirical tests conclude that there is a U-shaped relationship between environmental information disclosure and corporate sustainable growth, which decreases and then increases, and the U-shaped relationship is transmitted through innovation inputs. The U-shaped relationship between environmental information disclosure and corporate sustainable growth is weakened by firm size and enhanced by equity incentives. In addition, further group analysis reveals that the above U-shaped relationship is more significant in non-state enterprises than in state-owned enterprises.